Flexible descriptor indexing for multimedia databases - Catalin Calistru (2005)
Current multimedia applications require efficient tools for modeling and search. While solid models must support a large variety of concepts like sets, sub-sets, part-of hierarchies and integrate standards like Dublin Core, MPEG-7 (descriptors, descriptor schemes), TV-Anytime, MPEG-21 (digital item, digital item adaptation, digital item identification), the search algorithms must deal with heterogeneous multimedia data (text, image, audio and video). The search in audiovisual data requires the use of heterogeneous metadata representing a wide range of features, from low-level ones (color, motion) to high level ones (subject, mood), or domain-dependent concepts. The current work is part of the development of a prototype Multimedia Database and addresses the problem of choosing the proper storage and search strategy for the descriptors in the multimedia database. It includes a review of the main applicable data structures and search techniques and a case study from the point of view of our system requirements.